Pengaruh Transverse Friction dan Kinesiotaping Terhadap Penurunan Nyeri Pada De Quervain's Syndrome - Bawono, Adicahyo; , Agus Widodo, S.Fis, M.Kes; , u Dwi Kurniawati, SST.FT, M.Kes (2016)
Background: Make a batik is holding canting used to draw on the fabric. In general, the batik workers pain at the base of the thumb or distal radius side of the forearm. Imogiri Bantul village Giriloyo 18 positive respondents experienced de quervain's syndrome with Finkelstain test (+), palpation prossesus styloideus pain, and pain during movement of the opposition. Objective: To identify different effects of transverse friction and kinesiotaping to pain cases of de quervain's syndrome. Methods: This research used in this study is quasy experiment (two-group pretest-posttest design), the total sample of 18 people from the purposive sampling. Instrument for pain used the VAS measured before (pre) and after (post) action. Test the level of influence of pre and post-test measures wilxocon with probability value <0.05 then Ho is rejected, then the effect of different test transverse friction and kinesiotaping therapy using the Mann-Whitney test. Result: There is the influence of transverse friction and kinesiotaping to pain de quervain's syndrome cases after the test statistic with each wilxocon obtained significance value (p) = 0.008 and (p) = 0,007. There are different effects of transverse friction and kinesiotaping to pain de quervain's syndrome cases with a value of significance (p) = 0.011Conclusion: There are different effects of transverse friction and kinesiotaping to pain cases of de quervain's syndrome. Keywords: transverse friction and kinesiotaping, painful case of de quervain's syndrome.